THU0152 SARCOPENIA IS ASSOCIATED WITH PERSISTENT DISEASE ACTIVITY DURING FOLLOW-UP OF RHEUMATOID ARTHRITIS. (June 2019) - Park, Dong-Jin; Kang, Ji-Hyoun; Xu, Haimuzi; Lee, Kyung-Eun; Lee, Shin-Seok
Abstract : Objectives: This study investigated the prevalence and impact of sarcopenia on clinical outcomes during follow-up in patients with rheumatoid arthritis (RA). Methods: We enrolled 294 RA patients from a single tertiary center. Data were collected at the time of enrollment and annually thereafter for 3 consecutive years. Sarcopenia was assessed by bioelectrical impedance analysis and defined as a relative skeletal mass index (RSMI) < 5.14 kg/m 2 in women and < 7.40 kg/m 2 in men. Univariate and multivariate analyses were performed to identify the association between sarcopenia and clinical outcome. Results: Of the 294 RA patients, 8.2% had sarcopenia at the time of enrollment. Patients with sarcopenia were more likely to be older ( P =0.001), male ( P =0.001), and smokers ( P =0.001), and to have a higher body fat mass ( P =0.034) and body fat percentage ( P =0.039), and a lower basal metabolic rate ( P =0.013), than non-sarcopenic patients. Biologic agents were more commonly prescribed to sarcopenic patients than to non-sarcopenic patients ( P =0.048). The sarcopenic patients had higher Physician Global Assessment (PGA) ( P =0.015), higher mean and delta tender joints ( P =0.007), higher mean and delta swollen joints ( P =0.007), and higher mean DAS28-ESR ( P =0.014) and DAS28-CRP ( P =0.020) scores than the non-sarcopenic patients. In the multivariate analysis, sarcopenia was significantly associated with male gender (OR = 0.112, 95% CI: 0.041–0.304, P <0.001), mean PGA score (OR = 1.680, 95% CI: 1.067–2.646, P =0.025), and mean DAS28-ESR score (OR = 4.477, 95% CI: 1.661–12.067, P =0.003). Conclusion: Sarcopenia at baseline was an independent predictor of disease activity during follow-up in Korean patients with RA. Our results provide a rationale for lifestyle interventions designed to maintain normal weight in RA patients and thus help control disease activity. Disclosure of Interests: None declared